A Deterministic Inventory Routing Model for the Single-period Problems with Finite Time Horizon - Mohd Kamarul Irwan Abdul Rahim; Rosman Iteng; Mohd Akhir Ahmad (International Journal of Supply Chain Management, 2017)
This paper considers the problem of managing inventory and routing problems in a two-stage supply chain system under a Vendor Managed Inventory (VMI) policy. VMI is an inventory management policy in which the supplier assumes the responsibility of maintaining the inventory at the customers while ensuring that they will not run out of stock. The delivery times to the customers are no longer agreed in response to customers' orders; instead the supplier indicates when each delivery takes place. Under the VMI policy, the planning is proactive as it is based on the available information rather than reactive to customers' orders. Thus, in this research, we assumed that the demand at each customer is stationary and the warehouse is implementing a VMI. The objective of this research is to minimize the inventory and the transportation costs of the customers for a two-stage supply chain system. The problem is to identify the delivery quantities, delivery times and routes to the customers for the single-period deterministic inventory routing problem (SP-DIRP) system with finite time horizon. As a result, a linear mixed-integer program is established for the solutions of the SP-DIRP problem